CHIC Risk Stratification System for Predicting the Survival of Children With Hepatoblastoma: Data From Children With Hepatoblastoma in China - Huang, Junting; Hu, Yang; Jiang, Hong; Xu, Yanjie; Lu, Suying; Sun, Feifei; Zhu, Jia; Wang, Juan; Sun, Xiaofei; Liu, Juncheng; Zhen, Zijun; Zhang, Yizhuo (Frontiers in Oncology, 2020)
The aim of this study was to compare the accuracy of the Children's Oncology Group (COG) risk stratification system to the Children's Hepatic tumor International Collaboration (CHIC) risk stratification system for predicting the prognosis of Chinese children with hepatoblastoma (HB).Clinicopathological data of 86 patients diagnosed with HB between January 2014 and December 2017 were retrieved. The study endpoints were the 1-and 3-year overall survival (OS) and diseasefree survival (DFS) were analyzed to evaluate the predictive value.The 1-, 3-year OS and DFS of the 86 patients were 86.0, 76.3%, and 74.4, 54.0 %, respectively.Univariate analyses revealed that age at diagnosis had a significant role in prognosis for both OS and DFS, along with PRETEXT staging and metastasis at diagnosis. Multivariate analysis showed that metastasis at diagnosis (HR 3.628, 95% CI 1.404-9.378, P=0.008), PRETEXT staging system (HR 2.176, 95% CI 1.230-3.849, P=0.008) and age at diagnosis (HR 2.268, 95% CI 1.033-4.982, P=0.041) were independent factors for OS. For DFS, the independent factors were the PRETEXT staging system (HR 2.241, 95 % CI 1.533-3.277, P<0.001) and age at diagnosis (HR 1.792, 95 % CI 1.018-3.154, P=0.043). Both COG and CHIC risk stratification systems could effectively predict the prognosis of children with HB for OS. For DFS, the CHIC risk stratification system was more effective. In addition, the CHIC risk stratification system had a higher c-index (OS 0.743, DFS 0.730), compared to the COG risk stratification system (OS 0.726, DFS 0.594).Age at diagnosis played a significant role in prognosis. Compared to the COG risk stratification system, the CHIC risk stratification system was superior in predicting the survival of Chinese children with HB.